Application of the origami shape in the development of automotive crash box. Issue 4 (30th June 2020) - Boreanaz, Mario; Belingardi, Giovanni; Maia, Ciro De Faria
Abstract: The application of the origami geometry is proposed to shape the vehicle front crash box. A numerical and experimental study is developed to design innovative efficient thin‐walled tubes used as crash box in the automotive field with the scope of absorbing energy in the initial phase of an impact event. This geometry consists of a preformed surface pattern that, when submitted to an axial load, collapses in a controlled progressive deformation of the structure and induces a homogenous folding. The goal pursued in adopting this particular geometry is to increase the amount of the energy absorption while using less material. Therefore, in addition to improving the performance of the component, it contributes to save material, weight, and space. The results reported in this paper confirm the potential of this origami geometry. The present study started with an extensive virtual analysis, followed by an experimental test campaign for confirmation. The virtual analysis initiated from a classic crash box, actually used on a car (that is our reference structure). Then an origami‐shaped crash box has been developed with roughly the same dimensions. As a first step, a sensitivity analysis has been performed through the numerical study to identify the most effective design parameters. Finally, in order to obtain the experimental confirmation of the obtained results, an experimental crush test campaign on specimens with the same geometry studied numerically has been executed. Prototypes of the origami‐shaped crash boxes were manufactured by steel sheet cold forming, cutting, and welding. Ten quasistatic axial crush tests were conducted in the FCA‐LATAM laboratory in Belo Horizonte and correlation between the virtual and physical results assessed.